2021
DOI: 10.1177/1086296x211030469
|View full text |Cite
|
Sign up to set email alerts
|

Picturebooks as Critical Literacy: Experiences and Perspectives of Translingual Children From Refugee Backgrounds

Abstract: This multiple case study is part of a larger investigation of literacy practices in “Our Home,” an after-school program that provides learning support to children from refugee backgrounds. I asked, “What happens when translingual children from refugee backgrounds respond to multicultural, transnational, and translingual picturebooks?” Informed by critical literacy theories, I illuminate the experiences and perspectives of four children as they interacted with and engaged in dialogic reading of picturebooks; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…This lack of diversity defies emerging research underscoring the value of more representative texts. Students prefer texts where they can identify with characters (Cartledge et al, 2016); they feel affirmed when their perspectives are considered in texts (Vehabovic, 2021); and they sometimes change their perceptions and beliefs when reading about cultures that are different from their own (Ginsberg & Glenn, 2020). In short, research studies have found significant benefits to providing students with diverse texts, offering them opportunities both to see themselves ("mirrors") and see the lives of others ("windows") through reading (Bishop, 1990).…”
Section: New Insights From Researchmentioning
confidence: 99%
“…This lack of diversity defies emerging research underscoring the value of more representative texts. Students prefer texts where they can identify with characters (Cartledge et al, 2016); they feel affirmed when their perspectives are considered in texts (Vehabovic, 2021); and they sometimes change their perceptions and beliefs when reading about cultures that are different from their own (Ginsberg & Glenn, 2020). In short, research studies have found significant benefits to providing students with diverse texts, offering them opportunities both to see themselves ("mirrors") and see the lives of others ("windows") through reading (Bishop, 1990).…”
Section: New Insights From Researchmentioning
confidence: 99%
“…The articles included in this section build on the assumption that literacy and literacy education are always embroiled historically, socially and culturally in ways that reflect and uphold inequitable power relations. These include accounts of studies that explore the schooled literacy experiences of children who become marginalised by westernised and exclusionary practices, for example: Verhabovic's (2021) Two articles in this group address policy directly. Innes (2021) explores the effects on literacy policy on one school that joined an academy chain, while Willis (2019) draws on an analysis of policy and research on reading interventions to argue that reading research has been complicit in the reproduction of racial inequalities.…”
Section: Literacy and Power (15 Articles)mentioning
confidence: 99%